Análise dos atributos do processo de escolha veicular para movimentação urbana de cargas - Batista, Larissa Almeida Matias de Lima (2018)
The decision of vehicular mode choice by the companies to freight transportation in urban areas requires considerable effort, mainly by the growth in complexity of the urban freight distribution process that the results of the crisis in the mobility model adopted in the large Brazilian cities. With this, there are attributes that influence the commercial vehicle choice by the decision makers that are related to different sets of variables, such as those related to the vehicle, the cargo, the delivery region, restrictions resulting from external policies and the requirements from the operation, as just-in-time production systems. Recognizing this challenge, the objective of this paper is to seek a better understanding of the decision making regarding the commercial vehicle choice in urban freight transport in Brazil, through the identification and analysis of its key factors. The Methodology of Systematic Review (MSR) was conducted in order to review the literature about the attributes considered in the modal choice of freight transportation. A survey was carried out in order to verify the adherence of these attributes to the studied reality. Through these steps, we can analyze synergy between the attributes found in the literature and the factors considered important by logistics managers of decisions in choice of commercial vehicular mode in urban areas in Brazil. By the analysis of these results, it was possible to design a research experiment of stated preference, which was applied in carriers from all over Brazil. Discrete choice modeling technique, particularly multinomial logit, was used to quantify the relationship between decisions on the choice of commercial vehicular mode and their affecting factors. The results of the modeling were analyzed and was verified that the main attributes are: scheduling compliance, circulation constraints as per the size of the vehicle, accessibility of the delivery / collection, existence of suitable place for loading and unloading, age of vehicle, size of vehicle and use of the type of vehicle chosen by the customer.